Kesesuaian Materi Buku Almanya 2 Dengan Kurikulum 2013 Dalam Keterampilan Menulis Bahasa Jerman Tema Familie Kelas XI Semester Gasal - Perdana, Amalia Putri; Samsul, Suwarno Imam (LATERNE, 2022)
Writing skill is one of the skills that must be mastered in language learning. Of course, this writing skill cannot be done easily, it takes writing practice so that the results obtained are satisfactory. Writing skills are also applied to learning German. Talking about the teaching process in learning, of course, cannot be separated from textbooks that refer to the 2013 curriculum and have been set by the Ministry of Education and Culture. One of E-Journal Laterne, Volume 11, Nomor2 , Tahun 2022 the textbooks used in learning German at SMA N 1 Tarik Sidoarjo is the book Almanya 2. This study discusses the suitability of textbooks with the applicable Kurikulum 2013. However, it is not only the Kurikulum 2013 that is used to examine the suitability of the textbooks in Almanya 2. Other supports are included so that the textbooks are said to be appropriate and appropriate. As stated by Muslich, an educational figure said that there are 3 conditions for the indicator to be declared appropriate or not the textbook used. The indicators expressed by (Muslich,2010:292-295) are as follows, 1) core competencies (KI) and basic competencies (KD), which are described and must contain the syllabus of the subject in question, 2) appropriate material content, 3) supporting documents such as language suitability at the appropriate level, good language communication, response to the use of language needs to be prioritized in the student's line of thought. The indicators that have been stated by Muslich serve as a reference for the feasibility of textbooks that are brought and used in research instruments. The purpose of this article is to determine the suitability of the Familie theme material in the Almanya 2 textbook to the Kurikulum 2013 for class XI odd semesters. This study uses a descriptive qualitative approach by taking data sources from the book Almanya 2. The data taken are practice questions related to family themes, various forms of practice questions are presented, such as short answers, essays, true/false and matching the right words in a sentence. as well as stories. The number of practice questions presented is 11 practice questions. From the results of the study using the suitability criteria in the Muslich indicator, namely with the appropriate requirements as a textbook, it has been found that 4 Almanya books are worthy of being said to be textbooks, and 1 criteria that are not in accordance with the Muslich indicators. Then for the feasibility test of the practice questions in the Almanya book with the Kurikulum 2013, it was found that there were 7 practice questions with results in accordance with the Kurikulum 2013, 1 practice questions were not in accordance with the Kurikulum 2013, and 2 practice questions did not match the Kurikulum 2013.